REVIEW: LEGUMINOSA UNTUK MENGURANGI EMISI GAS METAN BERLEBIH PADA SAPI PERAH - Raden Febrianto Christi; Ajat Sudrajat; Itang Purnama (Jurnal Peternakan (Jurnal of Animal Science), 2026)
The success of a dairy farm depends heavily on the management of the cattle. A good dairy farm must ensure three key aspects are met: breeding stock, feed, and management. Dairy farming significantly impacts environmental pollution as a contributor to methane gas emissions. This article presents effective solutions to mitigate the negative environmental impacts of dairy farm waste. Feed is a crucial component that requires attention because it impacts the rumen ecosystem, which directly impacts livestock productivity, particularly dairy cattle. Legumes are a suitable alternative feed for reducing excess methane in dairy cattle because they contain bioactive compounds, including tannins, saponins, and flavonoids, which can reduce methane production.